Head and Neck Injuries among Powered Scooter Users between 2010 and 2019 - Trapp, Luke P.; Sukumar, Nitin; Cristel, Robert T; Yu, Jeffrey (Facial Plastic Surgery, 2024)
Powered scooters, including electric scooters (e-scooters), have become an increasingly available and popular mode of personal transportation, but the health risks of these devices are poorly explored. We aim to quantify the increase in frequency of powered scooter–associated head and neck region injuries occurring yearly from 2010 to 2019, and to compare the frequency and severity of injury with those involving unpowered scooters. Here we present a retrospective cross-sectional study of all patients with head and neck injuries associated with powered and unpowered scooters seen in emergency departments reporting to the National Electronic Injury Surveillance System (NEISS) database from January 1, 2010 to December 31, 2019. During this time frame, a total of 1,620 injuries associated with powered scooters and a total of 5,675 injuries associated with unpowered scooters were reported to the NEISS. The database estimates these to reflect a nationwide total of 54,036 powered scooter–related injuries and 168,265 unpowered scooter–related injuries. Powered scooter injuries have increased for both children and adults since 2014, and estimated powered scooter injuries (16,243) surpassed estimated unpowered scooter injuries (14,124) when including all age groups for the first time in 2019. In 2019, adults are estimated to have nearly twice as many powered scooter–related head and neck injuries as children (10,884 vs. 5,359, respectively). In 2019, a higher proportion of powered scooter–related injuries involving adults were severe injuries when compared with those involving children (13.3 vs. 5.2%, respectively). Interestingly, unpowered scooters still cause many more estimated injuries in children than powered scooters did during 2019 (11,953 vs. 5,083). We find that powered scooters are now associated with a greater number and severity of head and neck injuries among the adult population than the pediatric population. But unpowered scooters still cause more head and neck injuries than powered scooters in the pediatric population.
Keywords: head and neck injury; e-scooter; trauma